Mexico : Technical Assistance Report-Strengthening Public Assets and Liabilities Management. (IMF Staff Country Reports; Country Report ;, 2021)
The Ministry of Finance and Public Credit (SHCP) of Mexico intends to strengthen public asset and liability management (ALM) practices. The 2018 Fiscal Transparency Evaluation (FTE) identified several gaps in reporting public sector assets and liabilities and analysis of the associated risks. The authorities have identified the need for further reforms in three interrelated areas: (i) adopt the public sector balance sheet (PSBS) analytical framework to inform policy making; (ii) move toward more active cash management; and (iii) strengthen the management of financial assets and introduce a sovereign assets and liabilities management (SALM) framework in a phased manner. This report provides recommendations for reforms in these three areas.